2006
DOI: 10.1111/j.1469-8137.2006.01697.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional significance of dauciform roots: exudation of carboxylates and acid phosphatase under phosphorus deficiency in Caustis blakei (Cyperaceae)

Abstract: Summary• Caustis blakei produces an intriguing morphological adaptation by inducing dauciform roots in response to phosphorus (P) deficiency. We tested the hypothesis that these hairy, swollen lateral roots play a similar role to cluster roots in the exudation of organic chelators and ectoenzymes known to aid the chemical mobilization of sparingly available soil nutrients, such as P.• Dauciform-root development and exudate composition (carboxylates and acid phosphatase activity) were analysed in C. blakei plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 52 publications
3
74
0
Order By: Relevance
“…Both proteoid and dauciform roots are covered with dense mat of root hairs, which markedly increase the surface area of the root system and are also specialized in efficient synthesis and secretion of organic anions (especially citrate and malate) and phosphatases, which help to solubilize insoluble P resources and hydrolyze organic P for plant uptake (Playsted et al, 2006;Lambers et al, 2006). Cluster roots grown under P deficiency exude 20-to 40-times more citrate and malate than those grown under sufficient P (Vance et al, 2003).…”
Section: Cluster Root Formationmentioning
confidence: 99%
“…Both proteoid and dauciform roots are covered with dense mat of root hairs, which markedly increase the surface area of the root system and are also specialized in efficient synthesis and secretion of organic anions (especially citrate and malate) and phosphatases, which help to solubilize insoluble P resources and hydrolyze organic P for plant uptake (Playsted et al, 2006;Lambers et al, 2006). Cluster roots grown under P deficiency exude 20-to 40-times more citrate and malate than those grown under sufficient P (Vance et al, 2003).…”
Section: Cluster Root Formationmentioning
confidence: 99%
“…This phenomenon probably results from the fact that many Cyperaceae species produce dauciform roots. It has been suggested that their function is to acquire P from nutrient-poor, P-fixing soils by means of excretion of compounds such as carboxylates, phenolics, and phosphatases, which facilitate access to the sorbed P (Playsted et al 2006). The high autumn EC may be explained by the changes in the soil water regimes, as the water table in this part of the year was much lower than in the previous months, thus resulting in a more concentrated soil solution.…”
Section: Soil Propertiesmentioning
confidence: 98%
“…Root clusters in species of the Casuarinaceae Reddell et al 1997), Cyperaceae (Shane et al 2005;Playsted et al 2006), Fabaceae Keerthisinghe et al 1998), Myricaceae ) and Proteaceae (Lamont 1982;Aitken et al 1992;Shane et al 2003a;2003b) are suppressed when adding P to the root environment. Feeding P to leaves also suppresses cluster-root formation in L. albus (Marschner et al 1986;Gilbert et al 2000;Shane et al 2003a), showing that the signal(s) that leads to suppression of cluster-root initiation and growth originate in the shoot, most likely in young leaves (Keerthisinghe et al 1998).…”
Section: Effects Of Plant P Status On Development and Functioning Of mentioning
confidence: 99%
“…Though morphologically and anatomically very distinct, dauciform roots function in a way very similar to proteoid roots (Davies et al 1973;Lamont 1974;Shane et al 2005;Playsted et al 2006). That is, dauciform-root formation is suppressed when plants have a relatively high P status (Shane et al 2005;Playsted et al 2006) and carboxylates (e.g., citrate) are released during a brief interval once the dauciform root has matured ( Figure 1D, Shane et al 2005;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation